2003
DOI: 10.1530/rep.0.1250251
|View full text |Cite
|
Sign up to set email alerts
|

Selection of highly fertilization-competent bovine spermatozoa through adhesion to the Fallopian tube epithelium in vitro

Abstract: Mammalian spermatozoa undergo a marked reduction in number during their journey through the female reproductive tract. One of the checkpoints in the selection of fertilizing spermatozoa may be the transient adhesion to the Fallopian tube epithelium, an event previously shown to play a key role in sperm storage. Bovine spermatozoa adhering to the Fallopian tube epithelium in vitro may be synchronously released by sulphated glycoconjugates. In the present study, experiments were designed to quantify the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 18 publications
2
33
0
2
Order By: Relevance
“…There is also evidence from in vitro studies that sulphated glycoconjugates such as heparin can act on oviduct tissues to release sperm from binding (Talevi and Gualtieri, 2001;Gualtieri and Talevi, 2003;Gualtieri et al, 2005). However, very much in line with the overall theme of this essay, the concentrations of heparin or heparin-like glycoconjugates in oviduct luminal fluid are under cyclic ovarian control, reaching a peak during the period of oestrus (Parrish et al, 1989), so one returns to the perspective of gonadal coordination of pre-fertilisation events.…”
Section: Catecholamine and Ca 2þ Ionmentioning
confidence: 77%
See 1 more Smart Citation
“…There is also evidence from in vitro studies that sulphated glycoconjugates such as heparin can act on oviduct tissues to release sperm from binding (Talevi and Gualtieri, 2001;Gualtieri and Talevi, 2003;Gualtieri et al, 2005). However, very much in line with the overall theme of this essay, the concentrations of heparin or heparin-like glycoconjugates in oviduct luminal fluid are under cyclic ovarian control, reaching a peak during the period of oestrus (Parrish et al, 1989), so one returns to the perspective of gonadal coordination of pre-fertilisation events.…”
Section: Catecholamine and Ca 2þ Ionmentioning
confidence: 77%
“…Viewed at the molecular level, a remodelling of plasma membranes in different sub-populations of spermatozoa and in corresponding regions of the epithelium would be anticipated. Despite this emphasis on physiological control mechanisms, none of the preceding remarks is intended to deny that in-vitro binding assays using oviduct epithelial cells may offer a valuable new route towards sperm quality assessment, that is, a form of screening for potential fertility (De Pauw et al, 2002;Gualtieri and Talevi, 2003;Waberski et al, 2005Waberski et al, , 2006Petrunkina et al, 2007).…”
Section: In Vitro Models Of Sperm Bindingmentioning
confidence: 99%
“…It has been reported that, in different species, particular sperm subpopulations are selected by cell-cell adhesion in in vitro cultures with oviductal cells. Particularly in bovines, in vitro selected sperm are characterized by fertilization competence (Gualtieri & Talevi 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Bedford and Breed, 1994;Burkman et al, 1984;Overstreet and Cooper, 1975;Overstreet et al, 1980) and motility modulation has also been observed in spermatozoa exposed to oviductal fluid (McNutt et al, 1994). The sperm reservoir within the oviductal isthmus therefore contains a selected and highly fertile subpopulation of the original ejaculate (Ellington et al, 1999;Gualtieri and Talevi, 2003;Suarez, 1998) and it is unsurprising that measures of motility based on whole ejaculates show little correlation with fertility under competitive conditions such as heterospermic insemination.…”
Section: Introductionmentioning
confidence: 99%